2017
DOI: 10.1063/1.4992103
|View full text |Cite
|
Sign up to set email alerts
|

Optical losses in p-type layers of GaN ridge waveguides in the IR region

Abstract: Optical losses in c-plane (0001) GaN ridge waveguides, containing Mg-doped layers, were measured at 1064 nm, using the Fabry-Perot method. The losses increase linearly with the modal content of the p-layer, indicating that the absorption in these waveguides is dominated by p-layer absorption. The p-layer absorption is strongly anisotropic with E⊥c losses 4 times higher than E∥c. The absorption is temperature independent between 10 °C and 60 °C, supporting the possibility that it is related to Mg-bound holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Previous works present a detailed report of the design, fabrication and linear characterization of the GaN waveguides [25,28]. A brief description is provided here for completeness.…”
Section: Design and Fabrication Of Gan Ridge Waveguidesmentioning
confidence: 99%
“…Previous works present a detailed report of the design, fabrication and linear characterization of the GaN waveguides [25,28]. A brief description is provided here for completeness.…”
Section: Design and Fabrication Of Gan Ridge Waveguidesmentioning
confidence: 99%
“…The optical setup that is used to measure the WG transmission at different wavelengths is illustrated schematically in Figure . The setup details were reported previously, and are described here briefly. A narrow tunable laser source ( λ ∼ 1064 or 1550 nm) was coupled to the GaN WG using a lens.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the IR region, there are very few data . In a recent work, we have demonstrated that p‐GaN layers introduce high losses in the NIR region as well. Here, we describe this work briefly to provide a complete picture of the optical loss mechanisms that affect the p‐n WG modulator.…”
Section: Losses In P‐n Doped Gan Wgs Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, state of the art LDs have α i = 1 cm −1 and the maximum optical power is 7.2 W [4]. It was shown that, in the case of InGaN-based LDs, the high α i originates from light absorption in the Mg-doped layers [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%